Locus of Control as Determinants of Online - Dating Behaviour Among Graduates in Kwara – State - Ibraheem Islamiyyah Olajire; Esere Mary Ogechi (Universitas Komputer Indonesia, 2025)
This study investigated the influence of locus of control on online dating behaviors among university students in Kwara State. Employing a descriptive correlational survey design, data were collected from 380 students across four universities using adapted versions of the Online Dating Behaviour Scale and locus of control scale. Three null hypotheses were tested at a 0.05 significance level via Pearson Product-Moment Correlation. The findings demonstrated a significant positive correlation between online dating and an internal locus of control (r = 0.41, p < 0.05). Conversely, significant negative correlations emerged between online dating and both powerful others (r = -0.62) and chance (r = -0.26) loci of control. The study provides actionable recommendations based on these psychological determinants